Intercomparability of isotropic and anisotropic solar radiation models for different climatic zones of India. Issue 3 (13th August 2013) - Karakoti, Indira; Das, Prasun Kumar
<x xml:space="preserve">Abstract</x> In present communication, a methodology is described to compute total radiation falling on inclined plane by employing the measured global and diffuse radiation data on horizontal surface of India. Five stations Jodhpur, Kolkata, Bangalore, New Delhi, and Srinagar representative of five different climatic zones—hot and dry, hot and humid, temperate, composite and cold, respectively are chosen for the study. The measured data of 15 years (from 1986 to 2000) are exploited and statistical analysis is carried out for the monthly mean daily data. Isotropic model of Liu and Jordan and anisotropic model of Hay are applied in the estimation of total radiation on tilted plane facing south with various slopes and an inter‐comparison between these two models is made to ensure their adaptability in different climatic regions of India. Four tilt angles viz. latitude, latitude +15°N, latitude‐15°N and 22.5°N are considered and both the models are used for computation of total radiation to test whether variation in tilt angles affect the reliability of models for any particular climatic zone. Furthermore, for realistic predictions, accuracy of isotropic and anisotropic models is tested through three statistical parameters and isotropic model is found fit for first four climatic zones of India while for cold region, performance of anisotropic seems better. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 925–932, 2014